2007
DOI: 10.1345/aph.1k227
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Continuation of Stress Ulcer Prophylactic Therapy After Discharge

Abstract: Gastric acid suppressant medications initially prescribed for stress ulcer prophylaxis are frequently prescribed inappropriately on discharge for patients who were initially admitted to the medical/surgical ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
97
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(100 citation statements)
references
References 17 publications
0
97
1
2
Order By: Relevance
“…[4][5][6][7][8][9][10] There was no difference in error rates between patients cared for by hospitalists or cardiology attendings and those cared for by house staff, suggesting that clinical experience and expertise are not adequate protections against medication errors at discharge. By contrast, a recent study of an electronic medication reconciliation intervention demonstrated a reduction in provider errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8][9][10] There was no difference in error rates between patients cared for by hospitalists or cardiology attendings and those cared for by house staff, suggesting that clinical experience and expertise are not adequate protections against medication errors at discharge. By contrast, a recent study of an electronic medication reconciliation intervention demonstrated a reduction in provider errors.…”
Section: Discussionmentioning
confidence: 99%
“…3 A further set of errors can be made at the time of hospital discharge. [4][5][6][7][8][9][10] Errors include unintentional discontinuation of medication on discharge, [4][5][6][7] inappropriate retention of inpatient medications on discharge, 7,8 and inaccurate changes in dosing or frequency. Medication reconciliation inaccuracies accumulating at all these points of transition create substantial risk for medication errors on hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a large number of patients (n = 120), mainly in the "candidates" group, was discharged on AST. This practice is unjustified, and there is no evidence-based data that support the continuation of AST at discharge [57,58] . Furthermore, long-term use of acid-suppression medications was associated with an increase in unnecessary expenses [47,57] , and most importantly with an increased risk of pneumonia [59] , hip fracture [60] and Clostridium difficile colitis [61,62] .…”
mentioning
confidence: 99%
“…This practice is unjustified, and there is no evidence-based data that support the continuation of AST at discharge [57,58] . Furthermore, long-term use of acid-suppression medications was associated with an increase in unnecessary expenses [47,57] , and most importantly with an increased risk of pneumonia [59] , hip fracture [60] and Clostridium difficile colitis [61,62] . In order to explore whether teaching hospitals are more compliant with SUP guidelines, patients were stratified into two groups, resulting in statistically significant differences: a higher proportion of inpatients in teaching healthcare centers received adequate prophylaxis compared to patients in non-teaching hospitals.…”
mentioning
confidence: 99%
“…All these data on prescriptions are higher than those found in our population. Although most of these studies are old and based on evidence available at the time, the new scientific information on recommended use of antiulcer medications is one strength of this research regarding previous ones (20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%